Platelet indices in diabetics and influence of glycemic control – a hospital based study in North-East India - Bhattacharjee, Prasun; Datta, Abhijit; Kishore Debbarma, Rajesh; Kumar Das, Swapan (International Journal of Medical Research and Review, 2016)
Introduction: Platelets from patients with type 1 and type 2 diabetes exhibit enhanced platelet aggregation activity early in the disease course that may precede the development of cardiovascular diseases. Both atherosclerosis and thrombosis appear to contribute significantly to the increased cardiovascular risk of diabetic patients. Platelet indices include mean platelet volume (MPV), platelet distribution width (PDW), and platelet large cell ratio (P-LCR). This study was undertaken with the aim to find out the differences in platelet indices between diabetics and non-diabetics and also between patients with controlled and uncontrolled diabetes mellitus in a tertiary health care centre in North East India. Methods: This is a cross sectional study conducted in Agartala Government Medical College and GB Pant Hospital (AGMC & GBP Hospital). 100 cases and 100 controls were selected from the Diabetes clinic of Medicine out patient department (OPD) and Medicine wards. Platelet indices and HbA1C levels of these cases and controls were measured. Platelet indices were measured by a 3-part differential hematology auto-analyzer and HbA1C by High Performance Liquid Chromatography (HPLC) method. Blood glucose levels were estimated by oxidase-peroxidase method. Results: Platelet indices were found to be significantly higher among diabetics compared to non-diabetics and also they were found higher among patients with poor glycemic control with HbA1C>7% in comparison to patients with good glycemic control with HbA1C<7% (P value <0.05). Conclusions: Platelet indices are significantly increased in diabetics and the extent of increment is more in diabetics with poor glycemic control.